CARDIOVASCULAR RISK AMELIORATION IN THE METABOLIC SYNDROME - PRIMARY PROPHYLAXIS VS. SECONDARY PROPHYLAXIS - Irina Eşanu; Mihaela Boancă; Irina Cotea; Crînguţa Paraschiv; N. Forna (Romanian Society of Oral Rehabilitation, 2014)
Aim of the study The cardiometabolic risk is the sum of the traditional risk factors (high LDL-cholesterol, low HDL-cholesterol, dysglycemia, hypertension, smoking, age, and male sex) and of the metabolic syndrome components. The main goal of cardiovascular risk assessment in the metabolic syndrome (MS) is to identify the persons in need of pharmacological treatment. The answer to the question whether the cardiovascular risk associated with the metabolic syndrome is higher than the sum of the risk of its components seems to be affirmative.The purpose of our study is to assess the control of the cardiovascular risk factors in MS patients without cardiovascular events vs. MS patients with cardiovascular involvement. Material and methods The study included 107 patients who were divided into two groups. The first group included MS patients without cardiovascular involvement, and the second group comprised MS patients with cardiovascular involvement. The investigations methods were represented by anamnesis, clinical examination and paraclinical investigations, which included: EKG, glycemia and lipid profile (cholesterolemia, HDL-cholesterol, LDL-cholesterol, triglycerides). Cardiovascular involvement included ischemic heart disease, strokes, lower limb arteriopathy obliterans, chronic kidney disease, and advanced retinopathy. Results Total cardiovascular risk assessment is a basic patient management guidance tool, as it reflects the combined effects of several risk factors that may interact and sometimes enhance one another. No statistically significant differences were detected in the studied groups as concerns the blood pressure values, glycemia, LDL-cholesterol and triglycerides levels. Conclusions Cardiovascular prevention consists of assisting the persons with low absolute risk in maintaining this status throughout their lives and of helping those with high total cardiovascular disease risk to reduce it.